DNA CLEAVAGE, CYTOTOXIC ACTIVITIES, AND ANTIMICROBIAL STUDIES OF SOME NOVEL SCHIFF BASE TRANSITION METAL COMPLEXES DERIVED FROM 4-AMINOANTIPYRINE AND DIHYDROPYRIMIDONE OF VANILLIN - Mangaiyarkkarasi, P.; Arulantony, S. (International Journal of Current Pharmaceutical Research, 2016)
Objective: A novel series of transition metal complexes of Ni(II), Zn(II), Cd(II) and Hg(II) have been synthesized from the Schiff base derived from dihydropyrimidone derivative of vanillin (Biginelli Product) and 4-aminoantipyrine. Methods: The antimicrobial screening of the ligand and its complexes have been extensively studied on bacterias like E. coli, Vibrio spp., Staphylococcus aureus, Pseudomonas aeroginosa, Bacillus spp., Vibrio para haemolytic's, Salmonella spp., Aeromonas spp., Klebsiella spp., Proteus spp. and fungi such as Candida albicans, Aspergillus flavus, Pencillium spp., Aspergillus niger, Trichophyton. Results: The metal complexes show greater activity than ligand. The antimicrobial activity of the complexes follows the order Hg<Zn<Cu. The DNA cleaving activity of Schiff base ligand and its metal complexes was examined using, Hep 2 DNA as a target molecule by gel electrophoresis method. The Cu Complex-induced the DNA fragmentation with a specific activity. The in vitro cytotoxic effect of ligand and complex against Normal VERO and Hep2 was evaluated by MTT assay. Conclusion: The effect of [CuL2]Cl2 was found to be stronger than the other compounds even at its lower concentrations.